Metropolitan : The livest Magazine in America - Walker, John Brisben (New York City, 1895)
Metropolitan is an American magazine, published monthly from 1895 to 1925 in New York City. Former U.S. President Theodore Roosevelt was editor of the magazine during World War I when it focused on politics and literature. It was sometimes named, or called, Metropolitan Magazine or The Metropolitan, and its final issues were published as Macfadden's Fiction-Lover's Magazine. (wikipedia)
Https://en.wikipedia.org/wiki/Metropolitan_Magazine_(New_York_City)%20%20????
Engels
Tijdschriften